Development and Introduction of a Comprehensive Tobacco Control Policy in a Canadian Regional Health Authority - Diane Kunyk, RN, MN; Charl Els, MBChB, FC Psych, MMed Psych; Gerry Predy MD, FRCPC; Mary Haase, RN, PhD (Centers for Disease Control and Prevention, 2007)
BackgroundTobacco control policies in health care settings are necessary to protect patients, employees, physicians, visitors, and volunteers from the dangers of secondhand smoke. This report documents the process of developing and introducing a comprehensive tobacco control policy in one Canadian regional health authority.ContextCapital Health (CH), a health authority that has 30,000 employees and serves 1.6 million people, is responsible for 18 hospitals and primary care facilities, 33 continuing care facilities, 29 public health locations, and 9 community care facilities. CH recently determined that it needed to revise its tobacco control policy because its facilities had different directives regarding tobacco use, some of which did not reflect the best current knowledge about the health risks associated with exposure to secondhand smoke. MethodsThe new smoke-free policy needed to be developed and executed within a narrow time frame, which required careful planning as well as the support of patients and CH staff members. An essential part of the new policy was the prevention of nicotine withdrawal among people required to undergo involuntary tobacco abstinence. The plan also included an integrated screening, intervention, and referral process designed to optimize health benefits for patients and staff members who smoked, as well as for those who did not. ConsequencesCH decided to close all smoking rooms (including those in psychiatry, palliative care, geriatrics, eating disorder, and tuberculosis units), to ban smoking in outdoor areas, to stop all sales of tobacco products in CH facilities, to require smoke-free environments during home visitations, and to reject funding from the tobacco industry.InterpretationBy implementing a consistent ban on indoor and outdoor smoking, CH is contributing to a comprehensive tobacco control policy that is arguably a regional health authority's most profound opportunity for health promotion.